The role of SUMOylation in the neurovascular dysfunction after acquired brain injury - Luo, Pengren; Li, Lin; Huang, Jiashang; Mao, Deqiang; Lou, Silong; Ruan, Jian; Chen, Jie; Tang, Ronghua; Shi, You; Zhou, Shuai; Yang, Haifeng (Frontiers in Pharmacology, 2023)
Acquired brain injury (ABI) is the most common disease of the nervous system, involving complex pathological processes, which often leads to a series of nervous system disorders. The structural destruction and dysfunction of the Neurovascular Unit (NVU) are prominent features of ABI. Therefore, understanding the molecular mechanism underlying NVU destruction and its reconstruction is the key to the treatment of ABI. SUMOylation is a protein post-translational modification (PTM), which can degrade and stabilize the substrate dynamically, thus playing an important role in regulating protein expression and biological signal transduction. Understanding the regulatory mechanism of SUMOylation can clarify the molecular mechanism of the occurrence and development of neurovascular dysfunction after ABI and is expected to provide a theoretical basis for the development of potential treatment strategies. This article reviews the role of SUMOylation in vascular events related to ABI, including NVU dysfunction and vascular remodeling, and puts forward therapeutic prospects.